The Effect Of Spiritual Support Implementation Based On Transcultural Theory (ISST) On Implementation Of Worship To Patients Of Stroke - Zaini Arif, Ahmad; Bakar, Abu; Astuti, Puji (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Introduction: Stroke is generally known as an attacking disease, crippling and even able to kill humans. Besides having physical and psychological problems, stroke patients also have psychospiritual problems. The aim of the study was to analyze the effect of Transcultural Theory (ISST) spiritual support implementation on worship in Stroke Patients. Method: The design of this study was a Quasi-Experimental approach with pre-post-test control group design, the sample was 36 patients, divided into 2, treatment groups and controls were taken by simple random sampling technique. Data analysis using the Mann-Whitney test with α = 0.05. Results and analysis: The results showed that the difference in the implementation of the intervention group was ± (SD) = 7.22 ± (4.6) and the control group was ± (SD) 0 ± (0). The results of the Mann-Whitney Test, P = 0,000, meaning that there is an effect of transcultural theory-based spiritual support implementation (ISST) on the implementation of worship. Discussion and Counseling: Giving the Implementation of spiritual support based on transcultural theory (ISST) can improve the implementation of worship. Nurses can provide spiritual support based on transcultural theory (ISST) in stroke patients as an intervention in spiritual nursing care.